In vivo Measurements of Electric Fields During Cranial Electrical Stimulation in the Human Brain - Wang, Minmin; Feng, Tao; Jiang, Hongjie; Zhu, Junming; Feng, Wuwei; Chhatbar, Pratik Y.; Zhang, Jianmin; Zhang, Shaomin (Frontiers in Human Neuroscience, 2022)
Cranial electrical stimulation (CES) has been applied at various current levels in both adults and children with neurological conditions with seemingly promising but somewhat inconsistent results. Stimulation-induced spatial electric fields within a specific brain region are likely a significant contributing factor for the biological effects. Although several simulation models have been used to predict electric field distributions in the brain, these models actually have not been validated by in vivo CES-induced electric field measurements in the live human brain. This study directly measured the CES-induced voltage changes with implanted stereotactic-electroencephalographic (sEEG) electrodes in twenty-one epilepsy participants (16 adults and 5 children) and then compared these measured values with the simulated ones obtained from the personalized models. In addition, we further investigated the influence of stimulation frequency, intensity, electrode montage and age on electric fields in parts of participants. We found both measured voltages and electric fields obtained in vivo are highly correlated with the predicted ones in our cohort (Voltages: r = 0.93, p < 0.001; Electric fields: r = 0.73, p < 0.001). In white matter and grey matter, the measured voltages linearly increased when the stimulation intensity increased from 5 to 500 𝜇A but showed no significant changes (averaged coefficient of variation < 4.10%) with changing stimulation frequency from 0.5 to 200 Hz. Electrode montage, but not age, significantly affects the distribution of the electric fields (n = 5, p < 0.01). Our in vivo measurements demonstrate that the individualized simulation model can reliably predict the CES-induced electric fields in both adults and children. It also confirms that the CES-induced electric fields highly depend on the electrode montages and individual anatomical features.